Rien de Nouveau chez Rimbaud : sur l’attribution des Illuminations - Simon Gabay (Humanités Numériques)
Who wrote the Illuminations? In 2014, their authorship was contested by Eddie Breuil in his essay Du Nouveau chez Rimbaud: the collection would not be the work of Arthur Rimbaud, but of another poète maudit, Germain Nouveau. If certain arguments of Breuil may be attractive, this new attribution does not however seem to be confirmed by initial investigations carried out using the most recent computational methods used for authorship attribution. Thanks to support vector machines, we are not only able to say with a reasonable degree of certainty that the Illuminations were indeed written by Rimbaud, but also to explore his style at an infralexical level by unfolding the results proposed by the machine.